A comparative study of Lean implementation in higher and further education institutions in the UK. Issue 9 (5th October 2015) - Thomas, Andrew; Antony, Jiju; Francis, Mark; Fisher, Ron
Abstract : Purpose: – The purpose of this paper is to investigate and understand the differences that exist between educational institutions in the methods and practices employed in the development and implementation of Lean projects. Whilst many Higher Education Institutions (HEIs) are now starting their journey towards effectively implementing Lean, Further Education Institutions (FEIs) have treaded this well worn path many years previously and so the aim of this paper is to find what key features and issues FEIs have put in place to assist them in implementing Lean projects and whether HEIs can learn from such institutions. Design/methodology/approach: – The paper applies two research methods in an attempt to understand the differences between the institutions and hence understand the key features that can be used to better implement Lean initiatives. First, through a series of focus groups, the authors employ a low-level form of Group Consensus Theory in an attempt to understand the organisational dynamics surrounding the adoption of Lean. This is used to understand whether Lean improvement teams within FEIs implement such initiatives with the autonomy and support from senior management. Second, the same group members, detailed interviews were held in order to identify further and more specific information around the tools and techniques employed in the implementation of Lean initiatives in both HEI and FEIs. Findings: – The study found that although FEIs had much more experience in the design, development and implementation of Lean initiatives, the organisational infrastructure and dynamics towards driving Lean in FEIs was less well embedded in to the culture of the respective institutions than first thought and, that Lean had been developed and driven initially by a consultancy-based approach and around a tool-driven mentality. It was seen that whilst HEIs were generally slower in getting off the mark, there seemed to be more enthusiasm and willingness to drive such initiatives forward and in a more systematic and holistic manner even though some of the projects were in their very early stages of implementation. Research limitations/implications: – Whilst this work provides key information on how Lean initiatives are implemented across different institution types, the work has only looked at a very small sample of two teaching focused HEI and two FEIs. The work will need to be extended much more widely to incorporate a larger set of HEIs (both research and teaching focused) in order to provide a more complete map of Lean development in HEIs. Practical implications: – The aim of the paper is to provide Lean project leaders in HEIs with some additional key insights towards the cultural and organisation dynamics that exist in educational institutions other than HEIs in order to assist them in developing further and more comprehensive Lean programmes. Originality/value: – This paper is the first of its kind to study the organisational and cultural dynamics that exist between differing educational institutions in their approaches towards the implementation of Lean and business improvement programmes. The key features highlighted in this work raise important issues regarding the need and importance of developing team dynamics around project implementation.